The Muslim Market Festival (PAMFEST): A Phenomenon in Building a Sharia Business Community Through Islamic-Themed Activities at Transmart Palembang. (Jurnal Karya Abdi Bangsa, 2025)
This community service activity aims to assess the Effectiveness and understand the deeper meaning of the 2025 Muslim Market Festival (PAMFEST) as a strategic tool in building a sharia ecosystem for Muslim entrepreneurs in Palembang. This was driven by the desire to have a platform that integrates business, education, and entertainment activities in accordance with Islamic principles. This research employed a qualitative field method, focusing on phenomenology, conducted from 4 September to 7, 2025, at Transmart Palembang. Information was collected through observation, documentation, and semi-structured interviews with three key informants: the booth owner, the committee head, and visitors, who were selected using a purposive sampling technique. The findings of this study revealed that PAMFEST 2025 was considered very successful and comprehensive, attracting high public attention and supporting branding and increasing sales for tenants, including Umrah travel agents. The specialty of this event lies in its spiritual integration, where all activities are suspended during prayer times, resulting in an organic market experience that emphasizes the values of the afterlife. Overall, PAMFEST has successfully created a community that strengthens the Sharia business network and serves as a platform for education and the promotion of Islamic values. Despite this success, the main challenges faced are expanding the scale of the event and improving facilities for tenants.
Keywords: Islamic business; Muslim community; events; Muslim Ecosystem